TRADITION PRANAYAM TRAINING ASSESSMENT ON PHYSIOLOGICAL PARAMETERS - Dr. Harneet Singh; Mangaldeep (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
The aim of the study is to assess the effects of pranayam training tradition on certain physiological parameters among school going children. Two hundred school children (age range 13-16 years) registered in the class 6th to 10th, selected randomly to participate in the study. Subject was divided in two groups’ 100N control and 100N experimental groups.  Physiological Parameters measures were obtained at baseline and at the end of pranayam training programme. Student’s (T) test was followed out to examine pre- and post-test values. Data noted that pranayam exercises were associated with significant decreases (p < 0.05) in Cardiovascular endurance and Breath hold capacity with significant increases (p < 0.05) values. The authors’ statistics demonstrate considerable physiological changes significantly affected by pranayam exercises in school going children. Examining relationships connected with the effects of training on physiological aspects add new dimensions that can help in assessing, directing and developing pranayam training programmes.